Implementasi Kebijakan Pengarusutamaan Gender di Pemerintah Daerah Daerah Istimewa Yogyakarta - Sari, Rina Hap; Suryani, Dewi Amanatun (Universitas Sebelas Maret, 2023)
Gender mainstreaming (PUG) is a strategy built to integrate gender into an integral dimension of planning, drafting, implementing, monitoring and evaluating development policies and programs. In the implementation of development in the Special Region of Yogyakarta (DIY), there are still problems, especially in the health, education, and economic sectors which are obstacles in realizing gender justice and equality. This study aims to determine the implementation of PUG policies in the DIY Regional Government (Pemda DIY) by using indicators of 7 (seven) PUG prerequisites. The method used is a qualitative descriptive approach with data collection techniques through observation, interviews and documentation. Based on the results of the study, it shows that the implementation of PUG in the DIY Regional Government can be formally identified from the commitment that is to include gender issues in the RPJMD. From a policy perspective, there is a Governor's Regulation for the Implementation of PUG. PUG institutionalization is evidenced by the establishment of PUG Working Groups and focal points. Resources related to the PUG implementation budget through the APBD. Meanwhile, HR is carried out through training for ASN. Gender disaggregated data can be accessed through the SIGA and DATAKU applications. Gender analysis is carried out through GAP and GBS tools to ensure gender responsive budget amounts. Community participation is shown by the involvement of academics, mass organizations and NGOs in program activities. However, the obstacle to the implementation of PUG is because not all Regional Apparatuses have made program plans based on Gender Analysis and the effectiveness of PUG monev has not been optimal. Suggestions for strengthening PUG are providing introduction activities or training related to PPRG for new prospective employees, educating on understanding of disaggregated data for each Regional Apparatus, and allocating a special PUG budget, as well as strengthening the commitment of the PUG Working Group to conduct monitoring and evaluation of PUG and encouraging focal points to implement PUG.